Synthesis, characterization, and antibacterial activities of novel starch derivatives against E. coli and S. aureus - Sosa Santillán, Gerardo de Jesús (2022)
Three novel starch derivatives with antibacterial properties are synthesized through a rather simple multistep synthesis route. In a first step, sodium periodate oxidation of the hydroxyl groups (C2–C3) of starch yields a di-aldehyde structure, which is used to attach N,N-dimethylbenzylamine by Schiff base formation. Then, the amino groups of aminated starch are quaternized with three different ammonium salts (4-bromobutyl-pyridinium bromide, 4-bromobutyl-benzalkonium bromide, and 4-bromobutyl-quinolinium bromide). The different resulting products are fully characterized by FTIR, 1H NMR, and SEC analysis. Their antibacterial properties are evaluated against Escherichia coli and Staphylococcus aureus in vitro to obtain minimum inhibitory and bactericidal concentrations. All the starch derivatives show strong antibacterial activities against Gram-negative E. coli strain and Gram-positive S. aureus. Finally, hemolysis assays show that two of the starch derivatives obtained have no significant hemolytic effect on isolated human red cells.